Malignant mixed epithelial and stromal tumor of the kidney: Report of the first male case. (19th September 2012) - Suzuki, Toshiro; Hiragata, Shiro; Hosaka, Kyoko; Oyama, Toshio; Kuroda, Naoto; Hes, Ondrej; Michal, Michal
Abstract Mixed epithelial and stromal tumor of the kidney is a rare benign tumor that consists of both epithelial and stromal cells. To date, eight malignant cases have previously been reported in female patients only. We report the first case of malignant mixed epithelial and stromal tumor of the kidney in a male patient. A 67‐year‐old Japanese man receiving hormonal therapy for prostatic cancer was found to have a right renal cystic tumor and underwent right nephrectomy. Histologically, the tumor was composed of benign epithelial and stromal cells in addition to malignant undifferentiated stromal cells. Immunohistochemically, the malignant stromal component was positive for cluster of differentiation 99 and B‐cell lymphoma 2, but no chimeric transcripts for synovial sarcoma were identified. Finally, a diagnosis of malignant mixed epithelial and stromal tumor of the kidney was recorded. Urologists and pathologists should recognize that malignant mixed epithelial and stromal tumors of the kidney might occur in male patients receiving hormonal therapy for prostatic cancer.